Combining steam explosion with 1-ethyl-3-methylimidazlium acetate treatment of wood yields lignin-coated cellulose nanocrystals of high aspect ratio - Abushammala, Hatem; Goldsztayn, Ruben; Leao, Alcides [UNESP]; Laborie, Marie-Pierre (Springer, 2016)
Lignin-coated cellulose nanocrystals (CNCs) were extracted from the tropical wood Angelim Vermelho in a yield of 47 % based on wood cellulose content. The procedure combined a mild steam explosion process with a treatment using 1-ethyl-3-methylimidazolium acetate ([EMIM][OAc]). The resulting CNCs showed exceptional aspect ratios of 83 +/- A 18 for wood-based CNCs and crystallinity index of 76 %. Residual lignin coating and cellulose acetylation were detected during the procedure and are proposed to minimize the known crystallite thickening. As a result, CNCs in dimensions close to their native state in wood were recovered. Furthermore, this novel extraction of CNCs directly from wood circumvents the tedious purification process necessary for CNC extraction from pulp.
Keywords: Cellulose nanocrystal; Steam explosion; Ionic liquid; Wood